Prevalence, epidemiology, seasonality, and phylogeny of Anaplasma marginale in blood samples of goats collected from Punjab, Pakistan - Aziz, Muhammad Naveed; Irfan, Muhammad; Parveen, Asia; Asif, Muhammad; Ijaz, Maryam; Mumtaz, Sadia; Iqbal, Furhan (Springer, 2022)
Purpose In Pakistan, a major constrain to goat farming is the tick and tick-borne diseases that results in financial losses to livestock farmers. This study was conducted to report the molecular prevalence of Anaplasma (A.) marginale in goat blood samples collected during four seasons from Khanewal district in Punjab (Pakistan). Methods and results The mps1 gene of A. marginale was targeted in 900 blood samples that were collected on seasonal basis (n = 225 per season) and 6.6% (61/900) goats were found positive with A. marginale. Anaplasma marginale positive PCR products were sequenced and submitted to the GenBank. Prevalence of A. marginale varied with sampling season (P = 0.002) and it was highest in the summer (11.5%) followed by the autumn (7.6%), spring (5.3%), and winter seasons (2.7%) respectively. Anaplasma marginale prevalence varied significantly between goat breeds during the autumn (p = 0.01) and summer seasons (p = 0.02). Goats more than 2 years old and livestock farms where only goats were kept and dogs were associated with herds were risk factors for ovine anaplasmosis during different seasons. White and red blood cell counts and parameters associated with their counts were affected in A. marginale infected goats while studied serum parameters remained unaffected. Conclusion PCR is a reliable tool for the detection of A. marginale in goat blood samples. A relatively low prevalence of A. marginale in goats of Khanewal district was observed and the parasite prevalence in goats was higher in the summer (May until September) and autumn (October and November) seasons. Control measures are required to prevent tick-borne diseases in ruminants from Pakistan.
Keywords: Anaplasma marginale; Goat; msp1; DNA sequencing; Phylogenetic analysis